Carbon-supported Ni nanoparticles for efficient CO2 electroreduction. Issue 47 (14th November 2018) - Jia, Mingwen; Choi, Changhyeok; Wu, Tai-Sing; Ma, Chen; Kang, Peng; Tao, Hengcong; Fan, Qun; Hong, Song; Liu, Shizhen; Soo, Yun-Liang; Jung, Yousung; Qiu, Jieshan; et al.
Abstract : Carbon-coated Ni nanoparticles supported on N-doped carbon enable efficient electroreduction of CO2 to CO comparable to single Ni sites. Abstract : The development of highly selective, low cost, and energy-efficient electrocatalysts is crucial for CO2 electrocatalysis to mitigate energy shortages and to lower the global carbon footprint. Herein, we first report that carbon-coated Ni nanoparticles supported on N-doped carbon enable efficient electroreduction of CO2 to CO. In contrast to most previously reported Ni metal catalysts that resulted in severe hydrogen evolution during CO2 conversion, the Ni particle catalyst here presents an unprecedented CO faradaic efficiency of approximately 94% at an overpotential of 0.59 V, even comparable to that of the best single Ni sites. The catalyst also affords a high CO partial current density and a large CO turnover frequency, reaching 22.7 mA cm −2 and 697 h −1 at −1.1 V ( versus the reversible hydrogen electrode), respectively. Experiments combined with density functional theory calculations showed that the carbon layer coated on Ni and N-dopants in carbon material both play important roles in improving catalytic activity for electrochemical CO2 reduction to CO by stabilizing *COOH without affecting the easy *CO desorption ability of the catalyst.